Phrenic Nerve Injury: An Underrecognized and Potentially Preventable Complication of Pulmonary Vein Isolation Using a Wide‐Area Circumferential Ablation Approach. (19th July 2013) - Yong Ji, Sang; Dewire, Jane; Barcelon, Bernadette; Philips, Binu; Catanzaro, John; Nazarian, Saman; Cheng, Alan; Spragg, David; Tandri, Harikrishna; Bansal, Sandeep; Ashikaga, Hiroshi; Rickard, Jack; et al.
Phrenic Nerve Injury Introduction Phrenic nerve injury (PNI) is a well‐known, although uncommon, complication of pulmonary vein isolation (PVI) using radiofrequency energy. Currently, there is no consensus about how to avoid or minimize this injury. The purpose of this study was to determine how often the phrenic nerve, as identified using a high‐output pacing, lies along the ablation trajectory of a wide‐area circumferential lesion set. We also sought to determine if PVI can be achieved without phrenic nerve injury by modifying the ablation lesion set so as to avoid those areas where phrenic nerve capture (PNC) is observed. Methods and Results We prospectively enrolled 100 consecutive patients (age 61.7 ± 9.2 years old, 75 men) who underwent RF PVI using a wide‐area circumferential ablation approach. A high‐output (20 mA at 2 milliseconds) endocardial pacing protocol was performed around the right pulmonary veins and the carina where a usual ablation lesion set would be made. A total of 30% of patients had PNC and required modification of ablation lines. In the group of patients with PNC, the carina was the most common site of capture (85%) followed by anterior right superior pulmonary vein (RSPV) (70%) and anterior right inferior pulmonary vein (RIPV) (30%). A total of 25% of PNC group had capture in all 3 (RSPV, RIPV, and carina) regions. There was no difference in the clinical characteristics between the groups with and without PNC. RF PVI caused no PNI in either group. Conclusion High output pacing around the right pulmonary veins and the carina reveals that the phrenic nerve lies along a wide‐area circumferential ablation trajectory in 30% of patients. Modification of ablation lines to avoid these sites may prevent phrenic nerve injury during RF PVI.